Gut microbiota in children with split-dose bowel preparations revealed by metagenomics - Zou, Yu; Zeng, Sihui; Chen, Moxian; Li, Sufang; Fu, Qin; Zhou, Shaoming; Zhou, Jianli (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Split-dose polyethylene glycol (PEG) is routinely used for bowel preparation before colonoscopy. This study aimed to investigate the composition of gut microbiota and its functions in pediatric patients undergoing split-dose PEG bowel preparation for colonoscopy to understand the stability and resilience of gut microbiota.From September to December 2021, 19 pediatric patients were enrolled at Shenzhen Children's Hospital and 76 samples (4 time points) were analyzed using metagenomics. Time points included Time_1 (one day before bowel preparation), Time_2 (one day after colonoscopy), Time_3 (two weeks after bowel preparation), and Time_4 (four weeks after bowel preparation).Result: Alpha diversity comparison at both the species and gene levels showed a decrease in community richness after colonoscopy, with little statistical significance. However, the Shannon diversity index significantly decreased (P<0.05) and gradually returned to pre-preparation levels at two weeks after bowel preparation. The genus level analysis showed six genera (Eubacterium, Escherichia, Intertinibacter, Veillonella, Ruminococcaceae unclassified, and Coprobacillus) significantly different across the four time periods.Additionally, at the species level, the abundance of Escherichia coli, Bacteroides fragilis, and Veillonella parvula significantly increased at one day after colonoscopy before gradually decreasing at two weeks after bowel preparation. In contrast, the abundance of Intertinibacter bartlettii decreased at one day after colonoscopy but then recovered at two weeks after bowel preparation, reaching the preoperative level at four weeks after bowel preparation. Furthermore, five functional pathways (base excision repair, biosynthesis of ansamycins, biosynthesis of siderophore group nonribosomal peptide, flavonoid biosynthesis, and biosynthesis of type II polyketide products) were significantly different across the four time periods, with recovery at two weeks after bowel preparation and reaching preoperative levels at four weeks after bowel preparation.Conclusions: Gut microbiota at the genus level, species level, and functional pathways are impacted in pediatric patients undergoing split-dose PEG bowel preparation and colonoscopy, with recovery two weeks following bowel preparation. However, the phylum level was not impacted. Modifications in gut microbiota composition and function may be investigated in Metagenomics of bowel preparations future studies of bowel preparation. This study highlights the stability and resilience of gut microbiota among pediatric patients during bowel preparation.